Evaluating the Safety of Continuous Infusion Lidocaine for Postoperative Pain. Issue 9 (September 2021) - Schuler, Brian R.; Lupi, Kenneth E.; Szumita, Paul M.; Kovacevic, Mary P.
Abstract : Objectives: The aim was to evaluate the safety of intravenous lidocaine for postoperative pain and the impact on opioid requirements and pain scores Materials and Methods: This was a single-center, retrospective, single-arm analysis of adult patients who received intravenous lidocaine for postoperative pain from January 2016 to December 2019. Patients were excluded if they received lidocaine for any indication other than pain or if lidocaine was only given intraoperatively. The primary outcome of this analysis was to determine the incidence of adverse effects (AEs) and the reason for discontinuation of lidocaine. Secondary outcomes included median daily pain scores (visual analog scale and Critical-Care Pain Observation Tool) and opioid consumption (daily morphine milligram equivalents) 24 hours before infusion and during day 1. Results: A total of 452 patients were evaluated of which 298 (65.9%) patients met inclusion criteria. Of the 154 patients excluded, 153 did not receive lidocaine postoperatively. The median duration of infusion was 34 [20:48] hours with a median initial and maintenance rate of 1 mg/kg/h dosed on ideal body weight. In our analysis, 174 (58.4%) patients had a documented AE during infusion and 38 (12.8%) had lidocaine discontinued because of an AE. The most common AE was nausea in 62 (20.8%) patients and the most common reason for discontinuation was confusion in 8 (2.7%) patients. Daily morphine milligram equivalents ( P <0.001) and visual analog scale ( P <0.001) significantly decreased when comparing 24 hours before infusion and day 1. Conclusion: Although a majority of patients receiving lidocaine for postoperative pain experienced an AE, this did not result in discontinuation in most patients. Abstract : Supplemental Digital Content is available in the text.